Regeneration of natural grasp prehensions on underactuated robot‐hand through kinaesthetic guidance - R. Chattaraj; S. Khan; D.G. Roy; B. Bepari; S. Bhaumik (Electronics Letters)
Grasping postures on a human hand are generated by an effective combination of spatial motions and contact forces on individual finger linkages. The rich kinematic redundancy within its anatomy, poses critical control challenges, while emulating natural prehensile actions. A simplified grasp‐formulation resolution is presented, by proposing a virtual‐object imagery to define generic grasp enaction sequences. The same are conceived and controlled by a set of contact points on the imagined grasp‐sphere, whose spatial conformation is guided by a serial‐haptic interface. The kinaesthetic cognitions along with visual feed to an operator ushers a reliable framework for grasp execution and transfer to a robot hardware without resorting to supplementary mapping mechanisms. Stable grasps on the anthropomorphic robot set‐up portrays a systematic procedure to transcribe human‐like postural attributes, aided with somesthetic and visual sensations that are anticipated to steer remote operator controls.